Effect of Salicylic Acid on Alleviating of Electrolyte Leakage and Flower Organ Damage in Apricot (Prunus armeniaca L. cv. ‘Shahroudi’) - Morteza ALIREZAIE NOGHONDAR; Hassan BAYAT; Hossein NEAMATI (Notulae Scientia Biologicae, 2013)
One of the most important limiting factors in spread of apricot in Iran is late spring frost, which damages flower bud and decrease total yield of crop. It has been found that salicylic acid (SA) plays a beneficial role during plant response to chilling and freezing stresses. To evaluate the effects of salicylic acid on alleviating of cold stress, the flower buds (FBs) of Prunus armeniaca L. cv. ‘Shahroudi’ were sprayed at pink cluster stage with SA at 4 levels (0, 0.5, 1 and 2 mM) and were then exposed to artificial cold stress (4 h at -4°C) or without cold stress (+ 25). Experimental attributes including electrolyte leakage of FBs and percentage of damage (PD) of pistil, anthers and petals to temperature treatments were determined. The results showed that at -4°C the lowest and highest PD and EL of FBs were observed in application of 0.5 and 0 mM SA, respectively. The highest and lowest PD of flower organ and EL were obtained in application of 0 and 2 mM SA, respectively at +25°C. Based on the results of this experiment, SA alleviates the negative effect of cold stress on electrolyte leakage and flower organ damages in apricot cv. ‘Shahroudi’, depending on the concentrations of SA used.